Exposure to Indoor Volatile Organic Compounds and Hypertension among Thin Film Transistor Liquid Crystal Display Workers - Ta-Yuan Chang; Kuei-Hung Huang; Chiu-Shong Liu; Bo-Ying Bao (Atmosphere, 2020)
This cross-sectional study aimed to determine the concentration of indoor volatile organic compounds (VOCs) and to investigate the association between indoor VOCs exposure and the prevalence of hypertension among thin film transistor liquid crystal display (TFT-LCD) workers. A total of 20 canisters were used to collect VOCs samples in the array, cell and module areas over 12 hours and VOCs concentrations were analyzed by the gas chromatography with mass spectrum. Individual information of health examination and lifestyles by self-administrated questionnaire were provided by 155 volunteers. The multivariate regression models were used to evaluate the associations between VOCs exposure, blood pressure and the prevalence of hypertension. The four dominant VOCs were ethanol (1870.8 ± 1754.0 ppb), acetone (689.9 ± 587.4 ppb), isopropyl alcohol (177.1 ± 202.3 ppb) and propylene glycol monomethyl ether acetate (98.2 ± 100.8 ppb), which were identified with the highest level in the module area for ethanol and acetone and in the array area for the others. Subjects exposed to a total level of ethanol, cyclohexanone and toluene ≥ 2500 ppb had an increased systolic blood pressure of 5.95 mmHg (95% confidence interval: 0.20–11.71; p = 0.043) compared with those exposed to <2500 ppb. Exposure to mixed VOCs in the indoor environment might be associated with elevated blood pressure among TFT-LCD workers.